PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN, LIKUIDITAS, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR ANEKA INDUSTRI DI BURSA EFEK INDONESIA TAHUN 2014-2018 - Utami, Elfrida Anggun Kurnia; Puji Astutie, Dewi Saptantinah; Kristianto, Djoko (Universitas Slamet Riyadi, 2020)
High company value will be able to attract investors to invest in the company, so that it will support in maximizing the company's main objectives. The purpose of this research is to analyzing the effect of capital structure, firm size, liquidity, and dividend policy on value of company. This study uses secondary data in the form of financial statements of manufacturing companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The sampling technique in this study uses purposive sampling. Data analysis techniques used in this study are the classic assumption test, multiple linear regression analysis, the overall model test, the coefficient of determination test, and the hypothesis test. The results showed that the capital structure had a negative and significant effect on firm value. Company size has a positive and significant effect on firm value. Whereas liquidity and dividend policy do not affect the value of the company. Suggestions in this study include adding research periods, adding other independent variables, using analysis methods and other proxies for future research.